Transcutaneous Electric Nerve Stimulation Reduces Pathological Sensation of Mesh One Week after Open Inguinal Hernia Surgery: Follow-Up Results from a Randomized, Double Blind and Placebo-Controlled Trial - Audrius Parseliunas; Saulius Paskauskas; Violeta Simatoniene; Egle Kubiliute; Edvinas Dainius; Andrejus Subocius; Linas Venclauskas; Donatas Venskutonis (Medicina, 2022)
Background and Objectives: Quality of life (QoL) and chronic pain are important outcomes following hernia surgery. The long-term effects of Transcutaneous Electric Nerve Stimulation (TENS) on postoperative recovery are not well known. In this trial we investigated the role of TENS on QoL and on the incidence of chronic pain following inguinal hernia repair with mesh. Materials and Methods: A total of 80 male patients with elective primary unilateral hernia Lichtenstein repair were randomly allocated to receive TENS or a placebo-TENS procedure. The TENS group received conventional TENS twice a day on the first and second postoperative days. The intensity was set at 0–0.5 mA in the placebo-TENS group. General and hernia-specific QoL, as well as the incidence of chronic pain were assessed using SF-36v2 and the Carolinas comfort scale. Results: Less sensation of mesh was reported by the TENS group patients one week after surgery. At this time point, the mean sensation score was 6.07 ± 8.88 in the TENS group and 14.08 ± 16.67 in the placebo-TENS group (p = 0.029). Although at two days and one week postoperatively, TENS group patients tended to have less pain, less movement restrictions and better overall hernia-specific QoL, the differences were not statistically significant. At 6 months postoperatively, no incidence of chronic pain was found in either the placebo-TENS or TENS group. Conclusions: Conventional TENS applied in the early postoperative period following inguinal hernia repair with mesh was found to reduce mesh-related foreign body sensation one week after surgery. Promising results were also found for other QoL domains.